Influência do ângulo da bacia e do ângulo de Cobb sobre o padrão da marcha em mulheres acima de 60 anos - Oliveira, Leda Magalhaes de [UNIFESP] (2018)
Introduction: the dynamics of the head, arms and back is vital for maintaining, balance during gait with advancing age. Hyperkyphosis, common in the elderly requires compensations for maintaining balance and, consequently, alter the quality of posture and gait, increasing the risk of falls. Objectives: primary objective: to determine the participation of the pelvic and the vertebral column angles in gait and balance parameters in women over 60 years of age. Secondary objective: to evaluate the relationships of the pelvic and the vertebral column angles with clinical tests for gait and balance. Methods: this is a transversal study of elderly women without gait dysfunction and preserved cognition (MiniMental - MMSE> 24. Berg Scale (BS), timed up and go (TUG), comfortable and fast walk in 10 m, and fall questionnaire were used. The sagittal radiological evaluation was performed for Thoracic Cobb (TC) and Lumbar (LC), Pelvic Incidence (PI), Sacral Inclination (SI) and Pelvic Inclination (PeI). The gait evaluation was assessed by accelerometry in a 30-meter walk and the parameters evaluated were: step length, Root Mean Square (RMS ) of acceleration during walking, symmetry, step and regularity of the stride in the anteroposterior (AP) and vertical (V) planes. Results: fifty-five elderly women with a mean age of 72 years (SD=6) were recruited. FES-I-Brazil was 25.2 (6.6); BS 49.4 (3.8); TUG 9.9 (2.2) seconds; Comfortable walking 1.09 (0.19) m/s, fast walking 1.38 (0.24) m/s. The radiographic angles were: TC 52 (15°), LC 55 (17°), PI 57 (11°), SI 39 (11°) and PeI 17 (8°). Correlations of BS with IS (0,377) and PeI with 10m of fast walk (0.366); LC with SI angles (0.637) and PeI with SI (0.674) were observed. Regarding accelerometry, SI was associated with step length (p = 0.082) and symmetry (p<0.001) and step regularity (p <0.001) in the AP plane. Association was found between LC and RMS in the V plane (p = 0.076), stride regularity in AP (p = 0.016) and regularity of the V-step (p = 0.02). In addition, TC was associated with stride regularity (p = 0.026), step regularity (0.026); symmetry in the AP plane (0.034) and stride regularity in V plane (p = 0.01). Conclusion: In elderly women with preservation of functional capacity the angles of the spine and pelvis interfere with gait quality, particularly in the anteroposterior plane.